Is There a Doctor on Vápnafjǫrð(r)? Disability, Health, and Embodied Difference in Vápnfirðinga saga - Tirosh, Yoav (Scandinavian-Canadian Studies / Études scandinaves au Canada, 2026)
This article focuses on Vápnfirðinga saga [The saga of the people of Weapons’ Fjord], a somewhat less discussed member of the so-called Íslendingasögur. It will be argued that disability, health and embodied difference are in fact not only of interest to the author, but an organizing theme for the narrative as a whole. The article is structured around the plot’s advancement rather than thematically, a choice meant to show the discursive and practical development of attitudes towards embodied difference within the text.